Odpowiedź :
Odpowiedź:
Szczegółowe wyjaśnienie:
1.
I. -3x + 7 = -2
-3x = -9 / :(-3)
x = 3 odp A.
II. 1/2 y = -16 / *2
y = -32 odp. C.
2.
a) 2x - 13 = x² + 5 dla x = -3
L = 2(-3) - 13 = -6 - 13 = -19
P = (-3)² + 5 = 9 + 5 = 14
L ≠ P NIE SPEŁNIA !
b) x(x-3) = -x + 24 dla x = 6
L = x² -3x = 6² - 18 = 36 - 18 = 18
P = -x + 24 = -6 + 24 = 18
L = P SPEŁNIA
3.
(x+3)/2 - (x+4)/4 = 2 / *4
2(x+3) - (x+4) = 8
2x + 6 - x - 4 = 8 odp D.
4.
a) 8 - (4x-12) = 8x - (3x-2)
8 - 4x + 12 = 8x - 3x + 2
20 - 4x = 5x + 2
-9x = 2 - 20
-9x = -18 /: (-9)
x = 2
Spr. dla x = 2
L = 8 - (4x-12) = 8 - (8-12) = 8 + 4 = 12
P = 8x - (3x-2) = 16 - (6-2) = 16 - 4 = 12
L = P
b)
3/4 (2-3x) = -6 / *4
3(2-3x) = -24
6 - 9x = -24
-9x = -24 - 6
-9x = -30 / : (-9)
x = 30/9 = 10/3
Spr dla x= 10/3
L = 3/4 (2-3x) = 3/4 (2 - 3(10/3)) = 3/4 (2 - 10)= 3/4 * (-8) = -6
P = -6
L = P